Effect of Coffea canephora Aqueous Extract On Microbial Counts in Ex Vivo Oral Biofilms: A Case Study - Antonio, Andréa Gonçalves; Iorio, Natália Lopes Pontes; Farah, Adriana; dos Santos, Kátia Regina Netto; Maia, Lucianne Cople (Planta Medica, 2012)
In the present study, the ex vivo antimicrobial effect of brewed coffee was tested on oral biofilms. For this, unsweetened and sweetened (10 % sucrose) brewed light-roasted Coffea canephora at 20 % was used in biofilms formed by non-stimulated saliva from three volunteers. After 30 min contact with unsweetened and sweetened brews, the average microorganism count in the biofilms reduced by 15.2 % and 12.4 %, respectively, with no statistical difference among them. We also observed a drop of microorganisms in the biofilms after treatment with sucrose solution at 5 % compared to control (saline) and to sucrose at 1 % and 3 %. In conclusion, Coffea canephora extract reduces the microbial count in oral biofilm, and our data suggest that sucrose concentration in coffee brew can influence its antimicrobial property against the referred biofilm.
Keywords: Coffea canephora; Rubiaceae; antimicrobial activity; oral biofilm; chlorogenic acid; caffeine